The influence of burdened comorbid status on treatment outcomes of injured elderly patients with severe traumatic brain injury - Ju. A. Shcherbuk; V. I. Zakharov; A. Ju. Shcherbuk; V. V. Donskov; E. V. Cherepanova; A. A. Iakovlev; T. V. Sergeeva; M. V. Iakovleva (Вестник хирургии имени И.И. Грекова)
The objective was to research the effect of burdened comorbid status on the course of severe traumatic brain injury (TBI) in the elderly.Material and methods. 243 injured elderly patients (182 men and 61 women) with severe TBI and burdened comorbid status.Results. It was found that the postoperative period was characterized by more severe course of injury associated with the development of infectious and inflammatory complications.Conclusion. Early medical rehabilitation does not have a significant impact on the state of comorbid status, but is important in the prevention of infectious and inflammatory complications due to the early activation of the victims and the elimination of hypodynamia in intensive care and neurosurgical departments.